From Farm to Market: Assessing Blockchain’s Role in Transparency and Traceability in the Nepalese Agriculture Sector - Adhikari, Suyash Shankar (Nepalese Journal of Management and Technology, 2025)
This study investigates the role of blockchain technology in enhancing transparency and traceability within the Nepalese agriculture sector, with a focus on minimizing information asymmetry, preventing fraudulent practices, and strengthening trust across the farm-to-market value chain. A quantitative research design was adopted, and primary data were collected through structured questionnaires from 234 respondents, including farmers, traders, cooperatives, and supply chain intermediaries. The data were analyzed using descriptive statistics, correlation, and regression techniques to evaluate the impact of technological readiness, stakeholder collaboration, and institutional support on blockchain-enabled systems. The findings explain that blockchain significantly improves transparency by enabling real-time data sharing, ensuring product authenticity, and reducing transaction disputes across the supply chain. However, its adoption is constrained by several challenges, including low digital literacy, limited technological infrastructure, and high implementation costs. The regression analysis further indicates that technological readiness, regulatory support, and collaborative governance are critical drivers for effective blockchain integration. The study offers practical implications for policymakers, agribusiness managers, and technology developers to enhance supply chain efficiency, food safety, and market competitiveness.